Juridical Review of the Term of Land Rights in Ibu Kota Nusantara in The Perspective of Agrarian Law - Yohana Maranatha; Indah Dwi Qurbani; Trie Sulistiowarni (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the juridical aspects of the term of land rights granted to business actors in the Ibu Kota Nusantara as stipulated in Article 9 paragraph (2) of Presidential Regulation No. 75 of 2024 concerning the Acceleration of the Development of the Ibu Kota Nusantara which grants the term of Land Rights of Cultivation Rights up to 190 years, as well as Building Rights and Use Rights up to 160 years. This provision contradicts Law No. 5/1960 on Basic Agrarian Principles and raises concerns about the potential monopolisation of land by private investors. This research aims to analyse the implications of the application of the land rights Cycle Agreement stipulated in Perpres 75/2024 in terms of the hierarchy of laws and regulations and analyse the granting of the land rights period in Ibu Kota Nusantara with the principle of land tenure by the State.